1966
DOI: 10.1017/s0079497x00014377
|View full text |Cite
|
Sign up to set email alerts
|

Excavation of a Round Barrow on Overton Hill, North Wiltshire

Abstract: The barrow is No. 6b in L. V. Grinsell's list for the parish of West Overton (V.C.H. Wilts., 1, Part I, 1957). It stood some 400 feet to the north of the most northerly member of the conspicuous group of bowl and bell barrows that straddles the A.4 road on Overton, or Sevenbarrow, Hill, 4½ miles west of Marlborough (SU 11966835). Its position is marked on the OS. 6-inch map (SU 16NW), but not on the 1-inch (Sheet 157). The height above sea-level is about 580 feet.The subsoil is Upper Chalk, its surface broken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…This is of interest, as although charcoal‐packed pits have been found beneath some other Wessex barrow types (e.g. Smith and Simpson ), the practice is more reminiscent of activities found within and beneath ring cairns and enclosure barrows in the west of Britain (e.g. Wainwright et al .…”
Section: Saucer Barrowsmentioning
confidence: 99%
“…This is of interest, as although charcoal‐packed pits have been found beneath some other Wessex barrow types (e.g. Smith and Simpson ), the practice is more reminiscent of activities found within and beneath ring cairns and enclosure barrows in the west of Britain (e.g. Wainwright et al .…”
Section: Saucer Barrowsmentioning
confidence: 99%
“…This included stone axes and maces, belt rings, pulley-rings or toggles and shale rings and beads. The evidence from bronze daggers, ornamental gold-work, amber beads and sponge-finger stones was also considered (Smith and Simpson 1966;Gerloff 1975;Taylor 1979;Beck and Shennan 1991;Eogan 1994).…”
Section: Appendixmentioning
confidence: 99%
“…The approach to these assemblages is obstructed by inevitable problems of definition; Piggott (1973, 344) for instance suggested that a coherent assemblage was necessary to signify a specialist and that individual implements such as the hammer-stones found at Ames-bury G4 might merely be personal possessions. As always it is difficult to know where to draw the line but two Beaker associated leather-working assemblages at least seem clear, both associated with males: Amesbury 51 (Wiltshire; Ashbee 1978) and West Overton 6B (Wiltshire; Smith and Simpson 1966). It is difficult to identify further instances however although Ashbee (1978, 42) suggested that Aldro 116 Grave A (Yorkshire) -a male burial with Beaker, bronze awl, flint flake, horn core and roe deer antler -might also have been a leather worker.…”
Section: Contexts Of Production Ii: Household Technologiesmentioning
confidence: 99%